2019
DOI: 10.1186/s12957-019-1772-8
|View full text |Cite
|
Sign up to set email alerts
|

Pathological complete response by advanced hepatocellular carcinoma with massive macrovascular invasion to hepatic arterial infusion chemotherapy: a case report

Abstract: BackgroundAdvanced hepatocellular carcinoma (HCC) with macrovascular invasion has an extremely dismal prognosis. We report a rare case of multiple HCC with tumor thrombosis in the portal vein and inferior vena cava that was initially treated with hepatic arterial infusion chemotherapy (HAIC); later resection revealed pathological complete response.Case presentationA 75-year-old man presented with HCC in his right liver, with tumor thrombosis growing to the right portal vein and the inferior vena cava, and bila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…After referring to the relevant medical data regarding HCC tissues that have not yet received a pathological biopsy, tumor cells were found to show high proliferation and differentiation activity, and the pathological specimens of the liver often suffered from hemorrhage and necrosis. We hypothesized that there is a correlation between tumor hemorrhage necrosis and the malignant tumor phenotype[ 3 ]. Numerous studies have reported that[ 4 , 5 ] both apoptotic and inhibitory genes are involved in the occurrence and development of tumors.…”
Section: Introductionmentioning
confidence: 99%
“…After referring to the relevant medical data regarding HCC tissues that have not yet received a pathological biopsy, tumor cells were found to show high proliferation and differentiation activity, and the pathological specimens of the liver often suffered from hemorrhage and necrosis. We hypothesized that there is a correlation between tumor hemorrhage necrosis and the malignant tumor phenotype[ 3 ]. Numerous studies have reported that[ 4 , 5 ] both apoptotic and inhibitory genes are involved in the occurrence and development of tumors.…”
Section: Introductionmentioning
confidence: 99%